MULTIPLE INTELLIGENCES AND STUDENT SELF-REGULATED LEARNING BASED ON TEACHER PROFESSIONALISM - Wulandari, Ismi Ayu; Nurdin, Dian Kusmawati; Marlina, Rina; Mulyaningsih, Yeni; Susilawati, Wati (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
Professionalism has an important role to play in creating an effective learning environment and improving student achievement. In this context, multiple intelligences and student learning independence are considered as factors that have the potential to influence teacher professionalism. However, research on the relationship between multiple intelligences and student learning independence and science teacher professionalism is still limited, especially at the secondary education level. This study aims to analyze the relationship between multiple intelligences and student learning independence on science teacher professionalism. This study used a quantitative design using multiple intelligence assessment instruments and student learning independence, as well as science teacher professionalism assessment instruments. The research sample consisted of 62 science teachers and students at several secondary schools in Subang Regency. The results show that there is a negative correlation (-0.208) on the multiple intelligences variable and there is a positive correlation (+0.132) on the learning independence variable. The results of the F test show a significance value of 0.411 > 0.05 so there is no relationship between the two variables on the professionalism of science teachers. Teachers need to understand the diversity of students' intelligence and encourage their independent learning. The implication of this research is the importance of developing training programs for science teachers in integrating appropriate approaches to improve professionalism and student learning outcomes.